Mathematical critical thinking ability through Brain based learning model in view of self-regulated learning - Sahidun, Muh; Suyitno, Amin; Pujiastuti, Emi (International Journal of Trends in Mathematics Education Research, 2023)
The method used is quantitative with a quasi-experimental design. Data collection techniques using tests and questionnaires. Data analysis techniques by testing the increase in mathematical critical thinking skills and learning independence. The results showed that there were 23 students in the control class with a moderately critical category with a percentage of 71.875%. The critical category consists of 9 students with a percentage of 28.125%. In the experimental class there are 3 students in the critical category with a percentage of 9.375%. For the very critical category there are 29 students with a percentage of 90.625%. The results of the t test show that the P-value is 0.000 0.05, there is an increase in the ability to think critically mathematically through the brain based learning model. The results of the control class self-regulated learning were 5108 with a mean value of 63.85 in the fairly independent category. The experimental class is 6114 with an average value of 76.43 in the independent category. Test results with the t test show a P-value of 0.000 0.05, meaning that the class has independent learning in the experimental class.